Training for Disaster Response Youth Cadres About Post Earthquake Injury Using Student Centered Learning (Scl) Approach - septyana eka rahmawati; Eka Rudy Purwana; Hardiansyah hardiansyah; Dewi Purnamawati (Universitas Airlangga, 2023)
Efforts to deal with crises due to disasters or so-called disaster management are a series of activities that began before the occurrence of outbreaks and disasters which were carried out through prevention, mitigation (mitigating/mitigating the impact) and preparedness in dealing with outbreaks and disasters. In general, disaster management is aimed at preventing and limiting the number of victims, so there must be early intervention efforts made by people exposed to training so that the severity of the disaster does not occur. due to the earthquake at SMA Negeri 8 Mataram with a student centered learning (SCL) approach. This study uses a quasi-experimental design with one pre and post test design. A total of 40 Disaster Response Cadre (KATANA) cadres were given disaster response cadre training and disaster preparedness was measured before and after the training. Data analysis used paired t test. The results show that there is an effect of post-disaster intervention disaster response training on disaster preparedness with a p-value of 0.000 <0.05. Conclusion, the results of this study are expected to be a program innovation for youth cadres to improve disaster preparedness.